THE IMPACT OF NEOLIBERALISM ON EFL EDUCATION: A CRITICAL DISCOURSE ANALYSIS OF EDUCATOR EXPERIENCES IN SOUTH KOREA - Reyes, Cyril; Jung, Christina Dahee (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This paper explores the discourses used by English-as-a-Foreign Language (EFL) instructors in South Korea. The study uncovers the factors shaping educator perspectives through survey comments, semi-structured interviews, and a focus group discussion. A preliminary analysis of qualitative data reveals the impact of neoliberal policies. In recognition of the invaluable insight of EFL educators, the researchers employed critical discourse analysis (CDA) to expose how neoliberal ideology has changed EFL teaching in Korea. CDA highlighted how the language of disdain for the pursuit of profit harboured the potential for social transformation. As a result of CDA, this study demonstrates how money has become the nucleus of EFL teaching in Korea while the producers of cultural and financial capital, vis-à-vis the educators, are marginalized.